Leadership Styles and their Relationship to Job Performance among Workers in the Non-Profit Sector in Hafar Al-Batin Governorate (International Journal of Financial, Administrative and Economic Sciences, 2025)
This study aimed to determine the relationship between leadership styles (democratic, autocratic, liberal) and job performance among workers in the non-profit sector in Hafar Al-Batin Governorate in the Kingdom of Saudi Arabia. The study relied on the descriptive analytical approach, and to measure the variables of the study, a questionnaire was used, which was distributed to a sample of (170) of workers in the non-profit sector, and the study reached a number of results, most notably: that the democratic style came in the first rank in terms of the degree of verification among the administrative leaders in the non-profit sector in Hafar Al-Batin Governorate, followed by the free style, then in the last rank was the autocratic style, and there is also There is a correlation between leadership style and the level of job performance in the non-profit sector. The study recommended the necessity of raising leadership skills and trying to develop them through training plans and programmes, due to the importance of leaders having sufficient awareness of leadership styles affecting performance.
Keywords: Leadership Styles; Job Performance; Non-Profit Sector